Immunolocalization of FGF-2 and VEGF in rat periodontal ligament during experimental tooth movement - Milene Freitas Lima Salomão; Sílvia Regina de Almeida Reis; Vera Lúcia Costa Vale; Cintia de Vasconcellos Machado; Roberto Meyer; Ivana Lucia Oliveira Nascimento (Dental Press Editora, 2014)
OBJECTIVE: This article aimed at identifying the expression of fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor (VEGF) in the tension and pressure areas of rat periodontal ligament, in different periods of experimental orthodontic tooth movement. METHODS: An orthodontic force of 0.5 N was applied to the upper right first molar of 18 male Wistar rats for periods of 3 (group I), 7 (group II) and 14 days (group III). The counter-side first molar was used as a control. The animals were euthanized at the aforementioned time periods, and their maxillary bone was removed and fixed. After demineralization, the specimens were histologically processed and embedded in paraffin. FGF-2 and VEGF expressions were studied through immunohistochemistry and morphological analysis. RESULTS: The experimental side showed a higher expression of both FGF-2 and VEGF in all groups, when compared with the control side (P < 0.05). Statistically significant differences were also found between the tension and pressure areas in the experimental side. CONCLUSION: Both FGF-2 and VEGF are expressed in rat periodontal tissue. Additionally, these growth factors are upregulated when orthodontic forces are applied, thereby suggesting that they play an important role in changes that occur in periodontal tissue during orthodontic movement.